The Motive for the Pilgrimage to the Grave of Sheikh Syamsyuddin Hasibuan and its Impact in Sipare-Pare Hilir Village, Merbau District, North Labuhan Batu Regency - Atikah (Getpress Management Journals, 2023)
The practice of pilgrimage to the grave of Sheikh Syamsyuddin Hasibuan in Sipare-Pare Hilir Village has an important role in the culture and spirituality of the local community. However, understanding of the motives that drive the practice of pilgrimage is still limited. This research uses field studies by conducting in-depth interviews and participant observation to identify pilgrimage motifs specifically related to the tomb. The results of the analysis show that these motives are very diverse, including spiritual aspects despite the pros and cons, and local identities that are formed through the teachings of the congregation which are brought into social religious forms that take place in society. On the other hand, commercial factors play a part in increasing the number of pilgrims or visitors to graves. The large number of pilgrims can improve the economic level of the community around the pilgrimage site, pilgrimage organizers, and even become a source of regional income. Improving the infrastructure of pilgrimage sites is also an important factor in increasing pilgrims, because it attracts more people to come and use existing facilities. These findings provide an important contribution in filling the knowledge gap about pilgrimage practices in these locations, while highlighting the importance of preserving pilgrimage traditions and Islamic spirituality in Indonesia.